Proyecto pantallas humanas: publicidad multimedio interactiva móvil - González Jaramillo, Diana Cristina (2010)
This research aims to make feasible a study of a draft multimedia mobile interactive advertising. They are people with screens attached to his body, by a harness, who walk through different parts of a certain city carrying the advertising to another level, to differentiate the known methods of publicizing given product or service. What will the screens are encouraged to consumdor have the interaction with the advertiser. In the technological era, we must adapt, in case of advertising, to live up to what people desires. With mobile screens achieve direct communication with the consumer, it will implied that role can talk, give advice, become active. Additionally, for the contracting company advertising there is a saving of time and money because previously the time between the launch of an advertising campaign and to obtain the outcome was very extensive. Now, having high technology, time is reduced almost entirely by direct contact between the consumer and the environment advertising that is both a service provider.